Plano anual de auditoria interna da Rede Federal de Educação Profissional : uma análise das atividades realizadas pelas auditorias internas dos Institutos Federais do Nordeste brasileiro no período 2015-2017 - Caldas, Wenia Ventura de Farias (2019)
The control as an administrative function, studied by the Scientific Administration, has its origin in studies developed in the private sector. From the knowledge about the importance of control to the private institutions, this was incorporated to the public sectors. Specifically in Brazil, public administration began to recognize the importance of control in the nineteenth century, with the creation of the National Public Treasury Court. As a way of reaffirming the importance of control, a series of Laws and Decrees were issued, regulating and establishing the obligation for the organs to establish internal control units within their administrative structure. As a consequence of this obligation, the Federal Institutes of Education, Technology Science, and the Federal Executive Branch, instituted internal audit units to strengthen management, streamline control actions, and provide support to the Internal Control System Federal Executive Branch. In this context, the objective of this research was to analyze the activities carried out by the internal audit units of the FIs of the Northeast Region of Brazil, aimed at the accomplishment of the internal control purposes described in art. 74 of the Federal Constitution, in the triennium 2015-2017. The research is classified applied, descriptive, bibliographical, documentary, with application of online questionnaire, composed of closed and discursive questions. For data treatment, simple descriptive statistics were used for the closed questions, in the discursive questions the content analysis was used. There is an increase in the number of auditors in the period to which this survey refers. Regarding the planning of the activities, it was verified that the information presented by the PAINT of some institutions does not allow to detail the number of hours programs for each activity of the exercise, a fragility that makes it difficult to monitor the performance, both by the control bodies and by society. As a reflection of the difficulty of monitoring, it was verified that only two institutions fully complied with all activities foreseen in the triennium 2015-2017.